Moringa: An underutilized multipurpose powerful vegetable for nutritional security - Uikey, Pragya; Singathiya, Prakash; Sharma, Nikhil; Dixit, Gaurav (Indian Horticulture, 2026)
Moringa is a remarkable plant that has earned its reputation as a ‘miracle tree’ due to its exceptional nutritional, medicinal, and environmental benefits. From its nutrient-rich leaves and pods to its drought-resistant nature, the moringa tree’s significance extends far beyond its humble appearance. Furthermore, moringa is gaining popularity as a value-added ingredient in the production of functional foods. It has been widely used as a beneficial dietary supplement due to its strong defense against various illnesses and its ability to counter environmental toxins. Therefore, it is necessary to explore its potential applications and evaluate its medicinal properties, which could pave the way for developing new drugs and functional foods.